2005
DOI: 10.1007/s00122-005-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for yield and related traits in the wheat population Ning7840 × Clark

Abstract: Grain yield and associated agronomic traits are important factors in wheat (Triticum aestivum L.) improvement. Knowledge regarding the number, genomic location, and effect of quantitative trait loci (QTL) would facilitate marker-assisted selection and the development of cultivars with desirable characteristics. Our objectives were to identify QTLs directly and indirectly affecting grain yield expression. A population of 132 F12 recombinant inbred lines (RILs) was derived by single-seed descent from a cross bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
142
4
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(185 citation statements)
references
References 32 publications
34
142
4
5
Order By: Relevance
“…Comparative analysis with the known major QTL for yield in wheat: A survey of the literature reporting QTL for GY and related agronomic traits in both tetraploid and hexaploid wheat (Li et al 2002;Peng et al 2003;Elouafi and Nachit 2004;Huang et al 2004Huang et al , 2006McCartney et al 2005;Quarrie et al 2005Quarrie et al , 2007Marza et al 2006;Narasimhamoorthy et al 2006;Kuchel et al 2007;Kumar et al 2007;Ma et al 2007) revealed rather different scenarios for the two major GY QTL identified in our study. Our comparative analysis was carried out by relating the (LOD À 1) supporting interval of the QTL to the Ta-SSR-2004 consensus map (Somers et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative analysis with the known major QTL for yield in wheat: A survey of the literature reporting QTL for GY and related agronomic traits in both tetraploid and hexaploid wheat (Li et al 2002;Peng et al 2003;Elouafi and Nachit 2004;Huang et al 2004Huang et al , 2006McCartney et al 2005;Quarrie et al 2005Quarrie et al , 2007Marza et al 2006;Narasimhamoorthy et al 2006;Kuchel et al 2007;Kumar et al 2007;Ma et al 2007) revealed rather different scenarios for the two major GY QTL identified in our study. Our comparative analysis was carried out by relating the (LOD À 1) supporting interval of the QTL to the Ta-SSR-2004 consensus map (Somers et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…QTL for GY and PH have been assigned to the proximal region of chr. 2BL (Bö rner et al 2002;Marza et al 2006), and QTL for GY, kernel weight, and number of kernels per spike have been reported on chr. 2AL (Bö rner et al 2002;Peng et al 2003;Huang et al 2004;McCartney et al 2005), but not in the distal region.…”
Section: Discussionmentioning
confidence: 99%
“…For shortening the breeding cycle, the single seed descent technique (SSD) in combination with in vitro culture of immature embryos may be an alternative to the DH system. Currently, SSD populations are frequently used as alternatives to DH populations in genetic and genomic studies (see, for example, [12,13]). The SSD technique connected with embryo in vitro culture allows the attainment of homozygous lines in a relatively short time.…”
mentioning
confidence: 99%
“…Some of these genes have been *Corresponding authors (email: penghuiru@cau.edu.cn; qxsun@cau.edu.cn) exploited to breed many semidwarf cultivars with high yield potential. Recently, along with the advent of molecular quantitative genetics, about 50 quantitative trait loci (QTLs) for wheat plant height have been identified using the constructed molecular genetic linkage maps [3][4][5][6][7][8][9][10][11][12][13][14][15]. However, QTL mapping of plant height in wheat was only focused on the performance of this trait at the maturing stage.…”
mentioning
confidence: 99%